Differential impacts of nickel toxicity: NiO and NiSO4 on skin health and barrier function - Denisse Esther Mallaupoma Camarena; Mariana Corrêa Giannella; Julia de Toledo Bagatin; Silvia Romano de Assis; Tao Chen; Melanie Jane Bailey; Catia Costa; Ella Schneider; Johanna von Gerichten; Silvia Berlanga de Moraes Barros; Natalie Belsey; Silvya Stuchi Maria-Engler (Ecotoxicology and Environmental Safety, 2025)
Nickel is recognized as a potent skin sensitizer and a common cause of contact dermatitis. Nickel and its compounds are often associated with particulate matter in industrial settings. This study aimed to evaluate the effects of nickel oxide particulate matter (NiOPM) using in vitro skin models, and to compare the effects of NiSO4 topical application on healthy versus atopic dermatitis–sensitized skin. Key endpoints included histological analysis, cell viability, cytokine release, proliferation index, and protein expression. The results revealed that the reconstructed epidermal tissue representing healthy skin was properly stratified. After 24 h of exposure to NiOPM (0.4–4.6 mg/cm2), histological analysis and viability data (>50 %) indicated a lack of cytotoxicity related to irritation. However, ion beam analysis, immunofluorescence, cell proliferation (Ki67 marker), and inflammatory signaling (IL-1α, IL-8) suggest that prolonged exposure may be associated with increased epidermal permeability and oxidative stress, identifying NiOPM as a possible long-term sensitizer. In addition, comparative treatments of NiOPM vs. NiSO4 on models of healthy epidermis and with atopic epidermis, exposed for up to 72 h, demonstrate the damaging effect of NiSO4 as early as the first 24 h. Also, the results suggest differential effects on proliferative cell presence and loricrin expression. These findings indicate that elucidating the sensitization pathways of nickel is complex. The physicochemical characteristics of Ni compounds are closely related to exposure time, skin permeation capacity, and cellular damage.